Potential Utility of Oral Mucosal Capillaroscopy as an Indicator of Microvascular Damage in Behçet Disease: A Preliminary Study - Abdullah Demirbaş; Ömer Faruk Elmas; Gözde Ulutaş Demirbaş; Mustafa Atasoy; Ümit Türsen; Torello Lotti (Mattioli1885, 2021)
Introduction: Behçet disease (BD) is an auto-inflammatory condition characterized by multisystemic vasculitis. Oral mucosal capillaroscopy is an easy-to-use, repeatable, non-invasive method for evaluating mucosal microvasculature, contributing to the differential diagnosis and prognosis of various acute and chronic inflammatory diseases. Objectives: This study aims to characterize and describe the oral labial mucosal capillary findings in patients with BD using handheld dermatoscopy and to investigate the relationship between the capillary findings and the severity of the disease. Methods: This cross-sectional study included patients with BD and healthy subjects. Capillaroscopic examination of the oral labial mucosa in each subject was performed by a handheld dermatoscope using polarized light.   The clinical severity of BD was evaluated using Krause's Clinical Severity Scoring for BD. Results: Sixty patients with BD and 60 healthy subjects were enrolled in the study. The frequencies of irregular capillaries, microhemorrhages, glomerular vessels, megacapillaries, and tortuous vessels were statistically significantly higher in the patient group when compared to the healthy individuals. In addition, a correlation was detected between the oral mucosal capillaroscopic findings and disease duration, severity, and vascular complications. Conclusions: Our study is the first to explore the potential role of oral mucosal capillaroscopic examination in patients with BD. Data obtained from this study indicated that oral mucosal capillaroscopy may be a useful tool to demonstrate microvascular damage in patients with BD.